The Cabildo of the Twenty-four Electors of the Inca Royal Ensign of the eight Cusco parishes - Amado Gonzales, Donato (2008)
This article contains a general vision of the Council of Twenty-four Electors, an institution during the Viceroyalty which was created to elect the Alferez Real Inca who participated in the annual celebration in honor of Saint James the Apostle in Cusco. This institution was formed by the descendants of the Incan panacas (noble families), which were integrated within Indian parishes of the city. This study presents historical information about the origins of this institution, its importance in determining who was qualified for being considered as an Inca noble and to use the symbols, responsibilities and privileges of the aforementioned aristocracy. The article also shows the mechanisms by which the Incan nobility granted and received legitimacy from the Spanish Monarchical system.